PENERAPAN NILAI TASAWUF AKHLAKI DALAM ATURAN PONDOK PESANTREN: Studi Kasus di Pondok Pesantren Al-Inaaroh Darul Fikri Buntet Pesantren Cirebon - Afifudin Afifudin; Sri Maryati (Prodi Tasawuf dan Psikoterapi, Fakultas Agama Islam, Universitas Muhammadiyah Cirebon, 2022)
Morals are a very important foundation in the formation of human character. Morals can determine the quality of human values, not only for themselves but also for the people around them. The essence of Islam is also morals that can determine the quality of the relationship between a servant and his Lord, between a person and himself, between him and others, and between society and its environment. If all relationships are good, good morals will be created. But along with the times and globalization (advances in technology and science) greatly affect all aspects of human life, including morals. That is why this research discusses the importance of Sufism morals that are applied in Islamic educational institution, namely at the Al-Inaaroh Darul Fikri Islamic Boarding School in Buntet, Cirebon, West Java. This research uses qualitative research. In the data collection techniques used are interviews, observation, and documentation with a sociological approach. The results showed that the application of the value of Sufism morals in the rules of the Islamic boarding school on the social life of students (santri) in this pesantren is very influential. With strict sanctions and the practice of morals carried out together, the lives of the students gradually improved; no longer violating the rules of the Islamic boarding school. The ethics of the students when interacting with the surrounding community began to look better.